Accounting for Psychotropic Medication Changes in Prisons: Patient and Doctor Perspectives. (July 2015) - Hassan, Lamiece; Edge, Dawn; Senior, Jane; Shaw, Jenny
Psychotropic medicines are widely used to treat mental illness; however, people entering prison commonly report that prescribed psychotropic medicines are changed or withdrawn, adding to their distress in difficult times. Drawing on three extracts from a larger qualitative dataset in which patients and doctors were interviewed about psychotropic medication use in English prisons, we combined discursive psychological and Foucauldian discourse analysis techniques to examine how individuals accounted for medication changes. Patients used four discursive strategies to organize descriptions of medication changes: they established entitlement to psychotropic medication, questioned the clinical judgment of prison doctors; highlighted communication problems; and attributed negative health outcomes to medication regime changes. In contrast, we examined an effective defense by a general practitioner, which showed how clinical needs were prioritized over previously held prescriptions when making prescribing decisions. Wider implications for continuity and equivalence of care between prisons and the wider community are discussed.